KONSEP PEMIKIRAN AMIRUL ULUM DALAM BUKUNYA KARTINI NYANTRI DAN RELEVANSINYA TERHADAP PENDIDIKAN ISLAM - Halidah, Noor; Qomariyah, Nurul (Program Studi PAI STAI Al Falah Banjarbaru, 2022)
ABSTRACT: This study proposes the concept of Amirul Ulum's thought in his book Kartini Nyantri and its relevance in Islamic Education. Seeing the fact that Kartini is a woman warrior and a fighter who demands justice so that women get a proper education like men. So that this research problem can be formulated as follows: How is the concept of Amirul Ulum's thought in his book